2016
DOI: 10.1371/journal.pone.0151691
|View full text |Cite
|
Sign up to set email alerts
|

On Hunting Animals of the Biometric Menagerie for Online Signature

Abstract: Individuals behave differently regarding to biometric authentication systems. This fact was formalized in the literature by the concept of Biometric Menagerie, defining and labeling user groups with animal names in order to reflect their characteristics with respect to biometric systems. This concept was illustrated for face, fingerprint, iris, and speech modalities. The present study extends the Biometric Menagerie to online signatures, by proposing a novel methodology that ties specific quality measures for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…In order to assess signature vulnerability to attacks, we acquired 10 skilled forgeries per signature type after displaying on the screen the shape and kinematics of the target signature. This type of forgery is considered in the literature as being the best attacks [3,43,44]. We thus obtain 3700 skilled forgeries (74 × 10 × 5) done by different forgers.…”
Section: Signature Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess signature vulnerability to attacks, we acquired 10 skilled forgeries per signature type after displaying on the screen the shape and kinematics of the target signature. This type of forgery is considered in the literature as being the best attacks [3,43,44]. We thus obtain 3700 skilled forgeries (74 × 10 × 5) done by different forgers.…”
Section: Signature Data Acquisitionmentioning
confidence: 99%
“…These signatures are called "Reference signatures". In our previous works on signature quality assessment, we have shown that a signature's resistance to attacks depends on its information content, quantified by an entropy-based measure, called personal entropy [28,[40][41][42][43]. We identified automatically different risk levels in signatures related to three user categories, and in particular a "problematic" population, characterized by simple and highly variable signatures, very vulnerable to attacks.Based on these findings, we propose in this paper, since the enrollment phase on a touch screen sensor, a novel strategy that turns any signature with a "high risk" into a "low risk" one.…”
mentioning
confidence: 99%
“…The phenomenon of a "biometric menagerie", or "biometric zoo", has been observed in many biometric modalities and across several datasets [40,11]. These terms refer to the observation that the contribution of each user towards the overall FAR and FRR of a biometric system can vary significantly.…”
Section: Related Workmentioning
confidence: 99%
“…As a result, it is difficult to refine selection strategies to deal with problematic templates [25] thereby limiting the value of the quality metric. In addition, the concept of a user's personal entropy and relative entropy to infer a signature template's FRR and FAR against skilled forgery has recently been introduced by Houmani et al, in 2016 [11]. In their work, the proposed user's relative entropy for each signature template is derived from Kullback-Leibler distance between the local probability density functions of HMM model of genuine samples and that of skilled forgeries.…”
Section: Related Workmentioning
confidence: 99%
“…Houmani and Garcia-Salicetti [18] extended the Biometric Menagerie to online signatures and categorized the users of MCYT database using the Personal Entropy quality measure.…”
Section: Signaturementioning
confidence: 99%